Psychological Profile of Perpetrators and Psychological Impact on Victims of Child Grooming: A Systematic Literature Review - Emilia Afniyati Timung (CV. Publikasi Indonesia, 2026)
Child grooming is an increasingly concerning form of child sexual violence involving gradual emotional manipulation to establish trust, dependency, and control before sexual exploitation occurs. The development of digital technology has expanded opportunities for perpetrators to approach children through online platforms, making detection and prevention more challenging. This study aims to identify the psychological profile and modus operandi of child grooming perpetrators, examine the psychological impacts experienced by victims, and formulate implications for prevention and intervention strategies. This research employed a qualitative descriptive approach using a systematic literature review method. Data were obtained from five peer-reviewed scientific articles discussing child grooming and child sexual violence from psychological, legal, sociocultural, and intervention perspectives. The findings reveal that perpetrators generally apply sequential manipulation stages, including victim selection, gaining access and isolation, trust development, sexual desensitization, and post-exploitation control. Meanwhile, victims experience significant psychological consequences, including betrayal, traumatic sexualization, powerlessness, stigmatization, anxiety, depression, dissociation, sleep disorders, and post-traumatic symptoms. The study concludes that child grooming is a complex psychological and social phenomenon requiring multidimensional prevention through legal strengthening, trauma-based psychological interventions, comprehensive sexuality education, and collaboration among families, schools, communities, and law enforcement institutions.